On one class of pairs of n-surfaces in (n+2)-dimentional projective space; Bulletin of the Tomsk Polytechnic University; Vol. 311, № 2 - Luchinin A. A. (Mathematics and mechanics.Physics, 2007)
Заглавие с титульного листа